A method used to comprehensively evaluate dry and isentropic organic working fluids based on temperature-entropy (T-s) diagram. (15th January 2023) - Zhang, Xinxin; Li, Yang; Zhang, Yin; Zhang, Congtian
Abstract: Thermophysical properties of an organic working fluid greatly influence the thermodynamic performance of an Organic Rankine Cycle (ORC). Temperature-entropy ( T-s ) diagram is a useful and common tool used for analyzing thermodynamic state transition of working fluid and cycle performance. In a temperature-entropy ( T-s ) diagram, four areas are defined in the evaluation method proposed in this paper. The ratio of two areas, which are a curved triangle in near-critical region and a curved trapezoid in two-phase region, is used to evaluate the characteristics of working fluid. The ratio of the other two areas, which are a hexagon representing net output work of cycle and a rectangle representing the net output work of the Carnot cycle, is used to evaluate the cycle performance. On this basis, a comprehensive evaluation indicator that evaluates the characteristics of working fluid and the cycle performance simultaneously is established by dividing the above two ratios. Using the proposed method, dry and isentropic organic working fluids, which are often used in an Organic Rankine Cycle, are evaluated comprehensively. The evaluation method proposed in this paper may provide a reference for the design and actual operation of Organic Rankine Cycle system. Highlights: A comprehensive evaluation method based on T-s diagram is proposed. Four areas are defined in the evaluation method. The ratio of two areas is used to evaluate the characteristics of working fluid. The ratio of the other two areas is used to evaluate the cycle performance. A comprehensive evaluation indicator is established by dividing the above two ratios.